Ecological and economic benefits to cattle rangelands of restoring an apex predator. Issue 2 (18th December 2014) - Prowse, Thomas A. A.; Johnson, Christopher N.; Cassey, Phillip; Bradshaw, Corey J. A.; Brook, Barry W.; du Toit, Johan
Summary The conservation of terrestrial carnivores is hampered by economic conflicts between predation and livestock production. The dingo Canis dingo is the top predator in Australia's terrestrial ecosystems but its abundance is controlled because it preys on livestock. Dingo control (poisoning, shooting) is associated with increased densities of wild herbivores, which can lead to reduced cattle condition and fertility through competition for pasture. We investigated whether the restoration of dingoes might provide a net benefit for rangeland vegetation and the profit margins of cattle pastoralists. We developed a dynamic, multi‐species metamodel to represent the trophic linkages and economics of a rangeland cattle enterprise. To estimate the strength of dingo‐mediated trophic cascades, we underpinned the metamodel with a detailed simulation of pasture growth, grazing pressure and cattle live‐weight gain. An economic model that calculated the costs and revenues associated with maintaining the cattle herd was used to examine trade‐offs between livestock density, kangaroo abundance, calf losses and dingo control. We simulated the effects of dingo abundance on rangeland ecology (pasture biomass, kangaroo density) and enterprise performance (cattle live‐weight gain, gross margin). Assuming a typical stocking density for semi‐arid rangelands, we estimated that kangaroo control by an unbaited dingo population would increase pasture biomass by 53 kg ha−1, improve gross margins by 0·83 ha−1 and reduce inter‐annual variability in profits. The increase in pasture biomass due to dingoes was greatest at low stocking densities (that permitted high kangaroo abundance in the absence of predation), while improvement in profits was strongest at intermediate stocking densities (when cattle density was high enough to take advantage of the additional pasture biomass). At high stocking densities, the abundance of kangaroos was low, so if dingo abundance exceeded that required to control kangaroos, some dingo baiting could produce small economic gains. Synthesis and applications. There is little incentive for pastoralists to reduce livestock densities in mixed wildlife–livestock systems unless wildlife grazing can be controlled. Our results demonstrate that top‐down herbivore control by dingoes should allow cattle pastoralists to profit from conservative stocking densities while reducing the risk of pasture over‐utilization.